PRODUCTION OF CYCLODEXTRIN FROM TAPIOCA SUBSTRATE USING PULLULANASE AND CGTase SIMULTANEOUSLY - Amran Laga TIN (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTCyclodextrin is a modified starch which can be produced from the branched-chain of tapioca starch by the enzyme CGTase activity. This enzyme attacks the straight-chain of amylopectin of the substrate produced simultaneously by the hydrolyzing enzyme pullulanase on the tapioca starch. The aims of this research were to determine the best of temperature and reaction time on production step and to determine the best of concentration of the starch substrate to produce cyclodextrin. The temperature and reaction time applied were 50, 55 and 60 oC for up to 360 minutes and sampling was conducted every 30 minutes, while the concentration of starch applied were 20, 25, 30, 35 and 40% (w/v). Parameters measured were reducing sugar, starch residue, dextrose equivalent, viscosity and yield of cyclodextrin. The result showed that the branched-chain of starch was converted by the CGTase enzyme into cyclodextrin and reducing sugars. The best of temperature and reaction time for producing cyclodextrin were 60 oC and 210 minutes, respectively, which gave the highest conversion rate of cyclodextrin ( 70,10 %) on 20% (w/v) tapioca substrate. Furthermore, the best of concentration of the tapioca substrate was 30% (w/v) which gave the similar highest conversion rate cyclodextrin (69.96%) and yield (209.89 g/L). These were derived from the same condition of temperature and reaction time (60 oC and 210 minutes).Keywords: cyclodextrin, cyclization, hydrolyzing, substrate concentration, pullulanase and CGTase